Pensamento computacional educacional: ensaio sobre uma perspectiva libertadora - Couto, Gabriel Militello (2017)
This paper situates it self in the line of research Program of Graduate Studies in Education: Curriculum of the Pontifical Catholic University of São Paulo. It aims to reflect on the approximations between the concept of computational thinking and education in a liberating perspective. In order to do so, it leads to qualitative exploratory research on the subject by the survey of academic production of theses and dissertations produced at the Pontifical Catholic University of São Paulo (PUC-SP) and at State University of Campinas (UNICAMP), seeking the concept in titles, abstracts and keywords of 58,871 works carried out from 1965 to 2016. From this survey and analysis, the concept of “Computational Thinking for Education” is coined in a liberating perspective, based on the reflections on technology discussed in the works of Vieira Pinto and Milton Santos, of the concepts on Computational Thinking with the contributions of authors like Papert and Valente and liberating education, in the perspective given by Freire and Shor. This research concludes that computational thinking is an embryonic concept in the researched universities appearing in only one academic work and that it is not only possible to transpose computational thinking to basic education, but it is also possible to do so in a liberating way